TRIM25 inhibits infectious bursal disease virus replication by targeting VP3 for ubiquitination and degradation. - Suyan Wang (Public Library of Science (PLoS), 2021)
Infectious bursal disease virus (IBDV), a double-stranded RNA virus, causes immunosuppression and high mortality in 3-6-week-old chickens. Innate immune defense is a physical barrier to restrict viral replication. After viral infection, the host shows crucial defense responses, such as stimulation of antiviral effectors to restrict viral replication. Here, we conducted RNA-seq in avian cells infected by IBDV and identified TRIM25 as a host restriction factor. Specifically, TRIM25 deficiency dramatically increased viral yields, whereas overexpression of TRIM25 significantly inhibited IBDV replication. Immunoprecipitation assays indicated that TRIM25 only interacted with VP3 among all viral proteins, mediating its K27-linked polyubiquitination and subsequent proteasomal degradation. Moreover, the Lys854 residue of VP3 was identified as the key target site for the ubiquitination catalyzed by TRIM25. The ubiquitination site destroyed enhanced the replication ability of IBDV in vitro and in vivo. These findings demonstrated that TRIM25 inhibited IBDV replication by specifically ubiquitinating and degrading the structural protein VP3.